A localisation issue. Issue 6 (27th May 2022) - Midgley, Laura; Broad, Rebecca; Poole, Olivia; Flores, Lorena; Harikrishnan, Sreedharan; Lauckaite, Kristina; Moran, Nicholas
Abstract : A 65 year old lady presented with a one week history of chorea, dysarthria, behaviour change and imbalance. Her condition continued to progress with development of a motor axonal polyneuropathy, affecting mainly the distal upper limbs, and encephalopathy, with a Glasgow Coma Score (GCS) of 6. MRI head revealed non-specific white matter changes in the cerebral hemispheres. EEG showed a slow background and bifrontal triphasic waves. CSF testing revealed a lymphocytic pleocytosis (34/mm3) with elevated protein (0.88g/L). Extensive microbiological, genetic and autoimmune screening was negative other than positive IgLON5 antibodies (titre 1:1000). Treatment with intravenous methylprednisolone appeared to be unhelpful, however, plasma exchange was associated with resolution of the encephalopathy and distal upper limb weakness. Intravenous cyclophosphamide was given followed by oral mycophenolate. The patient remains clinically stable at one year after onset. Anti-IgLON5 disease is typically characterised by central nervous system involvement (sleep disturbance, chorea, gait imbalance and bulbar features) and an uncertain response to treatment. We have presented a case of this rare condition, unusual on account of the peripheral involvement (motor axonal polyneu- ropathy), and apparent improvement with immunosuppression. Laura.midgley1@nhs.net